VARIETY OF BRYOPHYTES IN SULTAN ADAM MANDIANGIN GRAND FOREST PARK AREA - Khairun Amalia; Ajizah, Aulia; Utami, Nurul Hidayati (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Moss plants can live well in areas that have high humidity. The Dutch Guesthouse which is located in the Sultan Adam Mandiangin Forest Park area has quite high humidity because the area has lots of dense plants, so it is a suitable habitat for the living nature of moss plants. This study aims to describe and identify the types of moss found. Data collection was carried out using the total roaming method, which was then followed by determining and identifying each sample of the moss plants found. Data analysis was carried out descriptively and identifying species with reference to the literature. The results of the study found 10 species of mosses belonging to 7 different families, both found in tree, rock and soil habitats. The species found were: Calymperes tenerum, Calymperes afzelii, Hyophila apiculata, Hyophila involuta (Hook.) A. Jaeger, Ectropothecium falciforme, Octoblepharum albidum, Philonotis hastata, Acroporium secundum, Lejeunea lamacerina, and Thysananthus sp. The results of this study are expected to provide information about the variety and biodiversity of mosses in South Kalimantan.